The impact of enhanced recovery after surgery on inflammatory indicators and prognosis related to complex appendicitis in children - Zhang, Jian-guo; Li, Hao-wei; Wu, Xiang-ming; Yu, Hai-bin; Liu, Yan-hui; Qi, Lin; Bai, Yu; Yang, Lin; Zhang, Hai-long; Wang, Xiao-yun; Jia, Yue-qi (Frontiers in Pediatrics, 2023)
Objective To explore the application effect of enhanced recovery after surgery (ERAS) perioperative plan in the treatment of complex appendicitis in children, and further enrich the implementation plan of ERAS in the field of pediatric surgery. Method This study selected 122 children who underwent laparoscopic complex appendectomy at Inner Mongolia Maternal and Child Health Hospital and Baotou Fourth Hospital from August 2018 to July 2022, and randomly divided them into a traditional surgery group (TS) and an enhanced recovery surgery group (ERAS). The changes of white blood cell (WBC), hypersensitive C-reactive protein (CRP), pro Calcitonin (PCT) and interleukin 6 (IL-6) before and after surgery were compared. The degree of pain, recovery time of intestinal function, length of hospital stay, hospital costs, postoperative complications and parental satisfaction were compared between the two groups. Result The WBC and CRP levels in the ERAS group at 6 hours after surgery, as well as the IL-6 levels on the 3rd day after surgery, were lower than those in the TS group. Meanwhile, the analgesic effect of ERAS group at 3 hours and 6 hours after surgery was better than that of TS group. And the ERAS group had a shorter postoperative first exhaust time, fewer overall hospital stays, and lower hospitalization costs. In addition, the ERAS group had high parental satisfaction during hospitalization. There was no statistically significant difference in postoperative complications between the two groups of children. Conclusion ERAS can promote postoperative recovery of children, reduce surgical stress, save family medical expenses, alleviate the pain of children, and improve parental satisfaction. It is a safe and effective method for treating complex appendicitis in children.